2007
DOI: 10.2223/jped.1710
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and insulin therapy in sepsis and critical illness

Abstract: Objetivo: Revisar a literatura sobre a fisiopatologia de hiperglicemia e controle glicêmico em crianças e adultos com sepse e doença crítica. Fontes de dados:Pesquisa não sistemática da literatura médica através da base de dados MEDLINE usando os termos hiperglicemia, controle glicêmico, terapia insulínica intensiva, sepse e terapia intensiva. Os artigos foram selecionados de acordo com sua relevância, conforme a opinião dos autores. Síntese dos dados:A hiperglicemia é freqüente em crianças com doenças crítica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…An RCT of strict glycemic control compared to moderate control using insulin in a pediatric ICU population found a reduction in mortality with an increase in hypoglycemia. Insulin therapy should only be conducted with frequent glucose monitoring in view of the risks for hypoglycemia which can be greater in newborns and children due to a) relative lack of glycogen stores and muscle mass for gluconeogenesis, and b) the heterogeneity of the population with some excreting no endogenous insulin and others demonstrating high insulin levels and insulin resistance [622][623][624][625][626][627][628].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…An RCT of strict glycemic control compared to moderate control using insulin in a pediatric ICU population found a reduction in mortality with an increase in hypoglycemia. Insulin therapy should only be conducted with frequent glucose monitoring in view of the risks for hypoglycemia which can be greater in newborns and children due to a) relative lack of glycogen stores and muscle mass for gluconeogenesis, and b) the heterogeneity of the population with some excreting no endogenous insulin and others demonstrating high insulin levels and insulin resistance [622][623][624][625][626][627][628].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…Insulin resistance is defined as the relative inability of insulin to increase glucose uptake and utilization and/or to suppress glucose production [147] and typically presents with hyperglycemia despite "normal" or increased insulin levels [148], although during infections, seemingly low insulin levels have been reported [149]. During illness, these alterations in glucose metabolism may differ in children compared with adults [150]. For instance, in children with meningococcal sepsis and shock, hyperglycemia and inadequate low insulin levels were found, which are compatible with an insufficient insulin response [151,152], whereas in children with meningococcal sepsis without shock, insulin resistance was found [151].…”
Section: Glucose Production and Uptake In Infectious Diseasementioning
confidence: 99%
“…These hormonal changes (also known as the counterregulatory response) and an increase in proinflammatory cytokines, i.e-interleukin (IL-1, IL-6), and tumor necrosis factor (TNF)-alpha, are important factors leading to hyperglycemia. 8 A high or low blood glucose level may have a significant effect on the outcomes in patients of neonatal sepsis. A recent study in Pakistan found that those patients of neonatal sepsis with altered glucose level had higher mortality.…”
Section: Introductionmentioning
confidence: 99%